2014
DOI: 10.1002/ajh.23656
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with bronchiolitis obliterans syndrome and chronic graft‐versus‐host disease after allogeneic hematopoietic cell transplantation

Abstract: Bronchiolitis obliterans syndrome (BOS) is a form of chronic graft vs. host disease (cGVHD) and a highly morbid pulmonary complication after allogeneic hematopoietic stem cell transplantation (HSCT). We assessed the prevalence and risk factors for BOS and cGVHD in a cohort of HSCT recipients, including those who received reduced intensity conditioning (RIC) HSCT. Between January 1, 2000 and June 30, 2010, all patients who underwent allogeneic HSCT at our institution (n = 1854) were retrospectively screened for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(36 citation statements)
references
References 39 publications
2
32
1
1
Order By: Relevance
“…In addition, Nakasone et al [14] have reported that female recipients, ABO mismatch HCT, a busulfan + cyclophosphamide-based conditioning regimen, and acute GVHD involving the skin were significant risk factors for the development of BOS. Recently, busulfan-based conditioning, an unrelated donor, and female donor were also reported as risk factors for BOS development [15]. In our present study, a busulfan-based conditioning regimen was found to be the only independent predictor of BOS development, which was consistent with previous studies [6,14,15].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, Nakasone et al [14] have reported that female recipients, ABO mismatch HCT, a busulfan + cyclophosphamide-based conditioning regimen, and acute GVHD involving the skin were significant risk factors for the development of BOS. Recently, busulfan-based conditioning, an unrelated donor, and female donor were also reported as risk factors for BOS development [15]. In our present study, a busulfan-based conditioning regimen was found to be the only independent predictor of BOS development, which was consistent with previous studies [6,14,15].…”
Section: Discussionsupporting
confidence: 92%
“…Recently, busulfan-based conditioning, an unrelated donor, and female donor were also reported as risk factors for BOS development [15]. In our present study, a busulfan-based conditioning regimen was found to be the only independent predictor of BOS development, which was consistent with previous studies [6,14,15]. It has been suggested that busulfan may cause direct toxicity to the epithelial lining cells of the lung, which can result in donor alloreactivity that contributes to the development of BOS [3,15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Показано также, что при использовании режимов кондиционирования со сниженной токсичностью LONIPC развиваются реже [21,22]. Однако применение бусульфана даже в режи-мах со сниженной токсичностью достоверно повыша-ет риск развития LONIPC [23]. Также доказанными факторами риска можно считать наличие хронической РТПХ (у 97 % пациентов с LONIPC), отсутствие анти-тимоцитарного глобулина в кондиционировании, не-родственные ТГСК, женский пол донора у реципиен-та мужского пола [23].…”
Section: патогенезunclassified
“…A busulfan-based regimen even in the setting of reduced intensity conditioning, use of an unrelated donor or female donor, pretransplant lung disease, acute GVHD, Cytomegalovirus (CMV)-positive status, and high-risk transplant were associated with increased risk of BOS. 24 On the other hand, antithymocyte globulin (ATG) was protective against GVHD and BOS. The study highlights the importance of busulfan as a risk factor for chronic GVHD and BOS.…”
Section: Bronchiolitis Obliterans Syndromementioning
confidence: 99%